Compact 4-Element beam steerable printed adaptive array antenna for 5G application - Selvaraju, R. R. (Institute of Electrical and Electronics Engineers Inc., 2016)
This article presents a design procedure of phase controlled linear adaptive array antenna operating at 38GHz for 5G application. The Wilkinson equal power divider/combiner feeding network is loaded with the antenna elements for equal power distribution. The Obtained gain of the antenna is 12dBi at the operating frequency of 38GHz. -15dB of isolation is observed between the array antenna elements at the operating frequency. The proposed antenna is simulated by using finite element method based on Ansoft HFSS software platform. The computed results are compared with experimental results revealing excellent agreement for wide range of frequencies. To avoid the substrate loss, low permittivity loss less RT/duroid substrate is used to design the proposed antenna.